Methodology for the preparation of a photographic historical information system for local history in Extremadura. The example of Los Santos de Maimona - Rubiano Montaño, Penélope; Vivas Moreno, Agustín; Nuño Moral, María Victoria (Revista General de Información y Documentación, 2019)
The purpose of this research is to establish a methodology for the creation of a Photographic Documentary Information System (SIDF) that allows us to study local history. The methodological resources used have been several: documentary techniques, which include the identification of the image and its documentary description through the adaptation of archival regulations, as well as the extraction of descriptors; information technologies, through the elaboration of a thesaurus that is inserted in an automated document manager, which is a tool that uses information and communication technologies to obtain more performance from the application; and, finally, the analytical methods, which are the analysis of images in all their aspects (formal, physical and conceptual). It is offered as a result a documentary manager that integrates the aforementioned methodological resources as support of works of the needed local history. All this is applied to the study of the trades of Los Santos de Maimona, a town in the province of Badajoz. Consequently, we conclude that the importance of photography as a documentary resource for the elaboration of collective memory requires SIDF as a procedure for searching and retrieving information.